A case of thyroid carcinoma with mucinous features harboring ETV6-NTRK3 fusion: Expanding the morphologic spectrum of NTRK-rearranged thyroid carcinoma - Khaled A. Murshed (14151927) (2022)
NTRK-rearranged thyroid carcinomas (NRTC) are rare. They are characterized by aggressive clinical behavior and distinct morphology. The presence of mucinous component in this subset of thyroid carcinomas is a finding that has never been described before. We report a 44-year-old female patient, who presented with a progressive enlarging anterior neck swelling for four months duration. Histopathologic examination of the resected thyroid gland demonstrated extensive infiltration of the left thyroid lobe by a carcinoma exhibiting dual morphology, partly composed of dilated glands filled with mucin and lined by mucous secreting cells, while other areas showed classical papillary thyroid carcinoma (PTC). Next Generation Sequencing (NGS) revealed a fusion between exon 4 of ETV6 gene and exon 14 of NTRK3 gene. Although rare, NRTCs should be correctly identified as they carry an actionable biomarker for emerging targeted therapies. Our case represents the first case of ETV6-NTRK3 translocated thyroid carcinoma with extensive mucinous features. Other Information Published in: Human Pathology Reports License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.hpr.2022.300623